2018
DOI: 10.1002/mnfr.201800885
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Early Glycation Products Promote the Growth of Prostate Tumors More than Advanced Glycation End‐Products through Modulation of Macrophage Polarization

Abstract: Scope Glycation products are ubiquitous in food at high concentrations in the Western diet. The well‐controlled glycation resulting in the production of early glycation products (EGPs) has been proposed as a strategy to improve the physicochemical properties of food proteins. However, the health effects of EGPs are unknown. It has been shown that the Western diet (glycation prone) is associated with a higher mortality in prostate cancer (PCa) patients than the prudent diet; therefore, the role of EGPs in prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Importantly, IL-10-deficient mice experienced severe T1D (Tian et al, 2001). In our previous studies, IL-10 was also identified as one of the most up-regulated cytokines/chemokines when EGPs was applied to human macrophages (PMA-differentiated-U937 cells), peritoneal macrophages from C57BL/6 females (Chen et al, 2018), and C57BL/6 males (Chen & Guo, 2019).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Importantly, IL-10-deficient mice experienced severe T1D (Tian et al, 2001). In our previous studies, IL-10 was also identified as one of the most up-regulated cytokines/chemokines when EGPs was applied to human macrophages (PMA-differentiated-U937 cells), peritoneal macrophages from C57BL/6 females (Chen et al, 2018), and C57BL/6 males (Chen & Guo, 2019).…”
Section: Discussionmentioning
confidence: 95%
“…In the small intestine, dietary protein antigens could induce periphery regulatory T cells (pTregs), which expressed high level of IL-10 and suppressed effector T cells (Kim et al, 2016). The consistently increased circulating IL-10 levels in both C57BL/6 males (Chen & Guo, 2019) and NOD females following EGP exposure suggested possible inductions of pTregs in the intestine, although other cells, such as M2 macrophages, CD4 + CD25 + Foxp3 − T cells ., regulatory B cells including CD19 hi CD1d hi CD5 + in mice (Yanaba et al, 2008) and CD24 hi CD27 + in humans (Iwata et al, 2011), could secrete IL-10 as well. In addition, the reduced intestinal absorption might increase the chances of gut fermentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous AGEs from food can be absorbed into the systemic circulation or cause inflammatory reactions at the colon level, as reviewed in [16]. The early glycation products from food were shown to promote prostate tumor growth more than AGEs [7]. Regardless of source (Maillard reaction or exogenous), AGEs may cause a direct destruction of the extracellular matrix or can trigger a receptormediated signaling cascade that results in the production of free radicals and proinflammatory molecules [28].…”
Section: Introductionmentioning
confidence: 99%